How is Integration Defined and Measured, and what Factors Drive Success in Brazil? An Integrative Review - Elaine R. Neiva; Gardenia Abbad; Maria Inês Gandolfo Conceição; Diana Lúcia Moura Pinho; Andreas Xyrichis (International Journal of Integrated Care, 2023)
Introduction: Integration in health and care can improve quality and outcomes, but it is challenged by expansion of medical knowledge, social pressures on patient needs, and demands to deliver critical information. In Latin American and in other lower and middle-income countries integrated care remains in development. This paper examined the available literature on integrated care to understand how Latin American countries identify and measure integration, and what factors influence success. Methods: This integrative literature review included systematic searches in Global Health, PubMed, SciELO and BVSPsi databases for articles on integrated care in Spanish, Portuguese, and English in the period from January of 1999 to December 2020. The articles were screened for selection and assessed independently by five reviewers that used the inclusion criteria of papers about integration in health care systems. The sample excluded articles that did not deal with the integration of health care, which addressed issues related to public health campaigns, programs to control endemics and epidemics, reports on the experience of implementing health services, health promotion guidelines, food safety, oral health, and books evaluation. Results: 24 articles were included: qualitative (75%), quantitative (12,5%), and mixed-method research (4%) published between 2000 and 2017. All studies were undertaken in Brazil, and two of them were also conducted in Latin American countries. In 15 articles there was an interchangeable use between concepts of integration of services and integrated care, while nine studies did not define integration. Barriers to integration included absence of shared understanding of knowledge among members of interprofessional teams, lack of clarity on professional roles, missing consensus on a definition and measurement of integrated care, power struggles between professionals, poor institutional support, insufficient team preparation and training and unequal valuation of professions by society. Conclusion: Several types of integration and factors contributing to the success of implementation of integrated care in various contexts in Brazil were identified. The concept of integration reflected the varied local and regional realities including different health settings and levels of health and care, suggesting a need for further clarifications on its objective and components especially in LMIC contexts.